BEST PRACTICE OF SHORT STORY WRITING WITH HYPNOTIC ENERGY AS POST-PANDEMIC INNOVATION (MENULIS CERPEN DENGAN HYPNOTIK ENERGI SEBAGAI KEGIATAN REFRESHING PASCA PANDEMI BAGI MAHASISWA) - Mimin Sahmini; Dadang Sunendar; Sumiyadi Sumiyadi; Isah Cahyani (Jurnal Gramatika, 2023)
The advancement of a nation can be seen in literary products. Writing is the key to the success and development of a person as they can produce short stories as literary works. Short stories are an example of literary works that contain fragments of indirect or direct life experiences. Messages and morals decided within a short story may reflect the author's values of life and characteristics. High motivation to start is required to develop the ability to present imagination and inspiration. Motivation is rooted in the power of one's mind thinking can change one's life. Motivation has a central role in writing, to have high motivation a writer must be able to penetrate the ego in the subconscious brain. The process of inputting suggestions and affirmations into the subconscious mind is crucial as it affects a person's behavior to write. If the message is already stored in the subconscious mind, a person will change his behavior into new values according to the implemented suggestions and affirmations. The power of the subconscious mind to influence behavior change by 80% is an opportunity and solution. Thus, hypnotic energy is suitable for a writing trick because it will change behaviors into new values. The method used in this research is descriptive qualitative. The researcher describes the surefire trick of writing with hypnotic energy based on conceptual studies from various books and journals. The results of this study produce a formula for writing tricks that make it easier for students to write.